Ecuador : Report on Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This data module of the Report on the Observance of Standards and Codes (ROSC) contains a summary assessment of dissemination practices in Ecuador relative to the IMF's Special Data Dissemination Standard (SDDS). It also presents an assessment of data quality for national accounts, consumer price, producer price, balance of payments, government finance, and monetary statistics, based on the Data Quality Assessment Framework (DQAF). The assessment reveals that Ecuador is in observance of SDDS specifications on coverage, periodicity, timeliness, and dissemination of advance release calendars for data subject to the SDDS.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet